Internal efficiency calibration for bulk samples using a peak-by-peak cascade technique. (2016) - Elmaghraby, Elsayed K.
A procedure for gamma ray detection efficiency calibration for bulk samples using an internal reference is proposed. The technique involves peak-by-peak cascade correlation to overcome the problem, arising when using standard reference material, due to diversity of attenuation to gamma ray among samples. The procedure is used for calibration for 214 Bi, 228 Ac, and all associated radionuclide using 40 K as reference. The experimental validation was done with environmental samples as well as neutron activated indium chloride sample. The peak-by-peak analysis results emphasise the effect of gamma ray attenuation inside the sample on the overall efficiency calibration and give the accurate calibration without need to more sophisticated procedures. The uncertainty analyses of the measurements of efficiency are discussed in order to minimise the systematic uncertainty.